Evaluating the teaching performance for the university teacher in light of the educational quality standards from the heads of departments and their deputies’ perspective views. The field of study at the university of Ammar thelidji laghouat. - Zalikha DJEKIDEL; Mohamed BOUFATAH (Social Sciences Journal, 2021)
This study aimed to evaluate the teaching performance in light of the educational quality standards from the heads of the departments and deputies’ perspective view at the university of Amar thelidji laghouat. To achieve this goal used eighteen collections of questionnaires and conducted them on a sample of twenty-eight heads of departments and deputies the study produced the following results:There are no statistically significant differences in the rated average of the respondents’ level of the teaching performance for the university teacher in light of the educational quality, due to the functional variables:Educational specialization, Academic grade, Years of experience.